Universidade, Ensino de Graduação e estágio curricular no curso de Direito - MOREIRA, Simone Dias (2008)
This study entitled: "University, teaching graduate and traineeship in the course of law" results from a literature search and document linked to the Line of Culture Research and Educational Process. Its object the study of university education, especially the sense of the traineeship in the course of law. To understand this process sought the meaning of the university source in the Medieval Europe in the XI century and in years 20 and 30 of the last century in Brazil. It shows that as time goes by that institution par excellence of thought and training has been narrowing its horizons in the direction of professionalization, the preparation for the world of work and therefore of learning to do. And so you lose the size of the mark and instituting training process. Hence the need and to interrogate its roots in the university, which was in its infancy to full of life, provoking the intellect, imagination and sensitivity of masters and disciples. That journey led us to question the meaning of education for graduation and put in other words the issue of the stage, the theory and practice and their relationship, not in terms of appearance, as if it were an addition, an addendum, who knows a lot important, but as realities while distinct, different and intrinsically linked. This research asked: what direction the university source in the Middle Ages? What is the meaning of the university located in Brazil? What is the genesis of education for graduation? What is the meaning of the traineeship in the course of law? Seeking unravel these issues, discussion was held with some authors that the sociocultural context facilitated the birth of the university in the Middle Ages as an institution par excellence of thought, the process of implementation of the juxtaposition of Brazilian university faculties, seeking evidence to support the theoretical understanding of education for graduation and the traineeship in the course of law. On the basis of: Coêlho (1987, 1994, 1998 , 1999, 2003, 2004), Chauí (1980, 1996, 1999), Cunha (1980, 1988, 1989, 2000) and others could discuss the meaning of the university, the teaching of graduation, the relationship between theory and practice, the direction of the stage and realize that the university is not exclusive locus of training for work, nor is effective probation role of such training.